Extraction and screening of antimicrobial properties from the fruits and roots of Morinda citrifolia Linn (Noni) plant. - Regalado, Aves B. (2002.)
Crude plant extracts were obtained from mature fruits and fresh roots of Morinda citrifolia L. plant and Tahitian noni juice (commercial product). Using Kirby-Bauer disk diffusion method, crude extracts were compared in terms of their antimicrobial activity against Staphylococcus aureus, Bacillus subtilis, Mycobacterium phlei, Escherichia coli, Pseudomonas aeuruginosa and Candida albicans. The fruit extract was found to be the most effective among the crude extracts showing moderate inhibitory activity in Staphylococcus aureus and lowest negative inhibition in Bacillus subtilis and control. The root extract followed next in the effectivity with weak inhibition in Staphylococcus aureus, and negative inhibitory activity in Bacillus subtilis, Mycobacterium phlei, Pseudomonas aeruginosa, Candida albicans and control. The commercial Tahitian Noni juice turned out to be the least effective with weak inhibition in Pseudomonas aeruginosa, and Escherichia coli; and negative inhibitory in Staphylococcus aureus, Bacillus subtilis, Mycobacterium phlei, Candida albicans and control. This study will be useful as a preliminary investigation on the feasibility of Morinda citrifolia L. plant as a future source of better medecines.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Plants -- Noni